2014
DOI: 10.5539/ijbm.v9n3p88
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Domestic and Cross-Border Acquisitions on Acquirer Shareholders’ Wealth: Empirical Evidence from Indian Corporate

Abstract: The present paper compares the impact of domestic acquisitions and cross-border acquisitions on Indian acquirer shareholders' wealth during [2003][2004][2005][2006][2007][2008]. A segregated analysis has also been conducted to measure the impact of stake/control acquired, based on a sample of acquisitions of 268 domestic and 255 target firms across border. Further, this paper also analyses the short-run performance of percentage of stake/control acquired in both type of acquisitions. The stake/control acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
(39 reference statements)
2
10
0
2
Order By: Relevance
“…Dananjaya dan Wiagustini (2015) menunjukkan bahwa tidak ada perbedaan abnormal return perusahaan yang signifikan sesudah dan sebelum melakukan merger. Rani et al, (2014) menunjukkan bahwa akuisisi lintas batas menghasilkan keuntungan yang lebih tinggi dari akuisisi domestik. Hal ini dapat dilihat dari abnormal return yang signifikan pada saat sebelum dan sesudah akuisisi.…”
Section: Review Literatur Dan Hipotesisunclassified
See 1 more Smart Citation
“…Dananjaya dan Wiagustini (2015) menunjukkan bahwa tidak ada perbedaan abnormal return perusahaan yang signifikan sesudah dan sebelum melakukan merger. Rani et al, (2014) menunjukkan bahwa akuisisi lintas batas menghasilkan keuntungan yang lebih tinggi dari akuisisi domestik. Hal ini dapat dilihat dari abnormal return yang signifikan pada saat sebelum dan sesudah akuisisi.…”
Section: Review Literatur Dan Hipotesisunclassified
“…Adanya perbedaan abnormal return yang signifikan juga kemungkinan disebabkan oleh para spekulan yang mencari keuntungan jangka pendek, dimana para spekulan tersebut kemungkinan orang-orang internal perusahaan yang mempunyai informasi tentang motivasi perusahaan melakukan akuisisi. Hasil penelitian ini sesuai dengan apa yang diteliti oleh Aritonang et al (2009), Rani et al (2014), dan Sehgal et al (2012).…”
Section: Pengujian Hipotesis Pertama (H1)unclassified
“…This might be due to the fact that this acquisition type may lead to higher return because synergy would materialise, as suggested by Song et al (2010a). In addition, as there is high information asymmetry and cultural barriers between target and bidder in CBMAs, full acquisition would ease the post-CBMA integration and improve firm's performance (Martynova & Renneboog, 2008;Rani et al, 2014). In the context of ASEAN firms, it is anticipated that full acquisition may explain the variation in firm's performance during CBMA as almost half of CBMA by ASEAN firms (46% of bidder and 41% of target) are full acquisition, as shown in Table 7.…”
Section: Determinants Unique To Asean Countriesmentioning
confidence: 99%
“…Many studies found that announcement of CBMAs created wealth for bidders (Bhagat, Malhotra, & Zhu, 2011;Cakici, Hessel, & Tandon, 1996;Chari et al, 2010;Corhay & Rad, 2000;Goergen & Renneboog, 2004;Lowinski, Schiereck, & Thomas, 2004;Martynova & Renneboog, 2008;Masulis, Wang, & Xie, 2012;Mueller & Yurtoglu, 2007;Rani, Yadav, & Jain, 2014;Yang, 2015;Zhu & Jog, 2012). Though, there were a few studies claimed that bidding shareholder loss following CBMA announcement (Aybar & Ficici, 2009;Bris & Cabolis, 2008;Cakici et al, 1996;Corhay & Rad, 2000;Ferreira et al, 2010;Jory & Ngo, 2011;Mangold & Lippok, 2008).…”
Section: Market Returnmentioning
confidence: 99%
See 1 more Smart Citation